GAMIFICATION AND STUDENT PERFORMANCE IN ELEARNING: AN EMPIRICAL STUDY - Jamil Ahmed; Fida Hussain Chandio; Syeda Hira Fatima Naqvi (Spectrum of Engineering Sciences, 2025)
Gamification is the intentional application of game mechanics and dynamics outside the context of games. This paper aimed to investigate the impact of gamification on students' academic performance under the context of an eLearning platform supported using the Moodle-based LearningZone LMS. Gamification components such as points, grades, badges, feedback, and leaderboards were integrated into the course. A quantitative quasi-experimental study design was employed. A total of 192 University of Turbat students, and Balochistan Residential College Turbat, participated in the study. Pre- and post testing examinations were administered to collect data. According to the paired samples t-test findings, the performance of the students improved significantly after the gamification intervention. A significant learning benefit of gamification was proven to be evidenced through the increase of the mean score from the pre test (35.49), to the post-test (40.71), with a t-value of 32.33 and p<0.001. The research indicates that to enhance the participation of the students, along with academic achievements, gamification has to be implemented carefully into eLearning aligned with the learning objectives. Educational institutions must ensure the provision of technical support to the learners to ensure an impactful integration of gamification in eLearning.